Investigation of Total Tannin, Phenolic & Flavonoid Content of Araucaria Heterophylla for Antioxidant Source - Ghosh, Ankita; Paul, Shimanta; Ghosh, Susmita; Akter, Sadia; Mahedi, Rezwan Ahmed; Afrin, Sadia; Hasan, Akayed; Sayeed, Md Abu; Syrmos, Nikolaos; Hasan, Ali Mohamod Wasaf (Journal of Tropical Pharmacy and Chemistry, 2024)
Secondary metabolites, a type of bioactive molecule with many functions, are abundant in Araucaria Heterophylla. The secondary metabolites flavonoids, phanolic acid, and tannin have been found to have anti-inflammatory, antiviral, antibacterial, antioxidant, and anticancer properties. The present study was conducted to analyze the phytochemical and determine the total flavonoid, tannin, phenolic content of Araucaria Heterophylla leaves extract using two different solvents (methanol and dichloromethane) using UV-Vis spectrophotometric. The plant was identified by NHB (ID No: DACB 48435) and prepared the methanolic extract to estimate the total content of tannin, phenolic & flavonoid in Araucaria Heterophylla. Folin-ciocaltu method was used for the investigation of total phenolic and tannin content. The A. heterophylla leaf methanolic and dichloromethane extract had remarkable antioxidant effects due to its high flavonoid and phenolic content. This standardised bioactive ingredient could be used in many phytopharmaceutical preparations